Case Report: Successful Treatment of Cutaneous Squamous Cell Carcinoma in Three Patients With a Combination of Acitretin and Clarithromycin - Zhao, Yan; Zhu, Yanting; Wang, Haiqing; Ji, Chao (Frontiers in Oncology, 2021)
Few studies have evaluated acitretin as a primary treatment for cutaneous squamous cell carcinoma (CSCC). We report, for the first time, three cases of CSCC successfully treated with acitretin and clarithromycin. A literature review on this subject was also was performed. This case report included three patients with CSCC treated with acitretin and clarithromycin at the First Affiliated Hospital of Fujian Medical University (2008 to 2019). Patient 1 (83-year-old woman, ulcerated mass on the left cheek), patient 2 (97-year-old woman, painful mass on the left cheek) and patient 3 (76-year-old woman, large mass on the right ankle) received 8, 6 and 30 courses of combination therapy. All patients tolerated the adverse effects (pseudotumor cerebri and mucocutaneous dryness) and achieved complete regression within 6 months. Patients 1, 2 and 3 have not experienced recurrence during a 10-, 3- and 6-year follow-up. Acitretin has limited efficacy as a monotherapy for CSCC. Our experience indicates that combination therapy with acitretin and clarithromycin may be an effective and well-tolerated treatment for unresectable CSCC.